Kebutuhan Spiritual Pada Pasien Kanker Dalam Menjalani Kemoterapi di RSU Dadi Keluarga - Siwi, Adiratna Sekar; Utami, Ririn Wahyu; Wibowo, Tophan Heri (Universitas Harapan Bangsa Purwokerto, 2023)
Background : Cancer is a disease in which the growth and spread of cells is not normal which causes death if not treated properly. One of the therapies performed on cancer patients is chemotherapy. Cancer can affect the physical, psychological, social, economic, and spiritual. Spiritual needs can be met from the family or the environment which can increase the enthusiasm of the respondents in undergoing chemotherapy. Purpose : This study aims to determine the spiritual needs of cancer patients undergoing chemotherapy at Dadi Keluarga Hospital. Method : This type of research is quantitative using a descriptive research design with a cross sectional approach. The sampling technique of non-probability accidental sampling using the slovin formula obtained results of 239 respondents. This study used the Daily Spiritual Experience Scale (DSES) questionnaire. Results : data are mostly aged 46-65 years as many as 117 respondents (49%), female sex 181 respondents (75.7%), duration of chemotherapy 1-6 months 193 respondents (80.8%), the most type of cancer is breast cancer 148 respondents (62%), education last graduated from elementary/junior high school, 110 respondents (46%), employment status is not working 173 respondents (72.4%), do not have a family history of cancer 190 respondents (79.5%). The results of this study showed that most of the high spiritual needs were 178 respondents (74.5%).